Islam in performance contemporary plays from South Asia - Sengupta, Ashis, 1962- (London Bloomsbury Methuen Drama, an imprint of Bloomsbury Publishing Plc, 2017)
Islam in Performance brings together six contemporary plays from Bangladesh, India, and Pakistan that highlight the political performance of Islam in South Asia, especially since the 1947 partition of the subcontinent. The plays invite comparison with one another, engaging with the issue from perspectives of the three countries concerned: Hindutva politics in India othering the Muslim population for electoral gains, radical Islamization of Pakistan paralyzing political governance and encouraging jihadi violence, and the ever-increasing Islamist threat to Bangladesh's founding secular ethos. Finally, this anthology focuses on the suffering such exclusionary politics of religious nationalism has piled upon minorities across the region. Widely performed but largely unpublished, the plays with their geographic and stylistic range provide a good spectrum of some of the best writing in contemporary South Asian drama. The editor's scholarly introduction offers a framework for studying the plays as both texts and performance pieces
Translated into English.
Includes bibliographical references.
Keywords: Islam in literature; Drama -- 21st century; South Asian literature -- 21st century